ANALISIS TATA KELOLA DALAM PENINGKATAN KESEJAHTERAAN PETANI KELAPA SAWIT (Studi Pada Koperasi Unit Desa (KUD) Makmur Rezeki di Desa Bulian Jaya Kab. Batang Hari) - Anas Fitri Nurjanah; Ahsan Putra Hafiz; Atar Satria Fikri (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2023)
Cooperatives are a people's economic movement whose all activities are based on the family principle. Governance is a structure and process in determining the direction and supervision of the company. This thesis aims to determine the governance of the Makmur Rezeki Village Unit Cooperative in its efforts to improve the welfare of oil palm smallholders, and the obstacles faced by the Makmur Rezeki Village Unit Cooperative. This research is a qualitative research, collecting data by means of interviews, observation and documentation. Informants in this study were administrators, employees and members of KUD Makmur Rezeki. Based on the results of the study it can be concluded: The Makmur Rezeki Village Unit Cooperative has made good efforts in maximizing the governance of implementation transparancy, akuntability, responsibility, indepedency, and fairness by providing good service, developing cooperatives, placing employees according to their portions, disclosing information and providing training to members. KUD Makmur Rezeki's efforts to improve the welfare of its members by buying oil palm fruit at relatively high prices, providing agricultural medicines, providing production facilities and providing a savings and loan business. The Makmur Rezeki Village Unit Cooperative has constraints in improving the welfare of cooperative members who come from within and outside the cooperative itself. KUD Makmur Rezeki should try to maximize governance by holding training and coaching for members and administrators of the Makmur Rezeki Village Cooperative Unit, holding outreach to members so they understand more about cooperatives.